Path Analysis on the Biopsychosocial Determinants and Genital Hygiene on Cervical Cancer at Dr. Moewardi Hospital, Surakarta, Central Java - Afriza Umami; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2018)
Background: Cervical cancer is the fourth most common cancer in women worldwide and the second most common cancer in women in developing countries after breast cancer. The prevalence of cervical cancer in Indonesia was 0.8‰ with an estimated 98.692 cases. This study aimed to determine the biopsychosocial and genital hygiene factors for cervical cancer.Subjects and Method: This was an analytic observational study with a case-control design, conducted at Dr. Moewardi Hospital, Surakarta, from December 2017 to February 2018. A total of 178 study subjects including 95 women with cervical cancer (case) and 83 women without cervical cancer (control) were selected by fixed disease sampling. The dependent variable was cervical cancer. The independent variables were the age at first sexual intercourse, a number of sexual partners, body mass index (BMI), stress, education, income, and genital hygiene. Cervical cancer data was collected by medical record. The other data were collected by questionnaire. The data were analyzed by path analysis model.Results: The risk of cervical cancer increased with the number of sexual partner >1 (b=1.91; 95% CI= 0.31 to 3.49; p=0.019), BMI ≥25 (b= 0.98; 95% CI= -0.06 to 2.04; p=0.067), and stress (b= 1.59; 95% CI= 0.39 to 2.80; p=0.009). The risk of cervical cancer decreased with higher education (b= -3.58; 95% CI= -4.77 to -2.39; p<0.001), higher income (b= -1.49; 95% CI= -2.73 to -0.25; p=0.019), age at first sexual intercourse ≥18 years (b= -1.36; 95% CI= -2.52 to -0.21; p= 0.020), and genital hygiene (b= -1.24; 95% CI= -2.35 to -0.13; p=0.028). Income increased with higher education (b= 2.48; 95% CI= 1.71 to 3.25; p<0.001). Genital hygiene increased with education (b= 1.16; 95% CI= 0.47 to 1.86; p=0.001). Age at first sexual intercourse ≥18 years increased with higher education (b= 1.30; 95% CI= 0.58 to 2.01; p<0.001). Stress increased with number of sexual partner >1 (b= 1.36; 95% CI= 0.12 to 2.61; p=0.032).Conclusion: The risk of cervical cancer increases with the number of sexual partners, BMI, and stress, but decreases with higher education, higher income, age at first sexual intercourse, and genital hygiene.Keywords: cervical cancer, biopsychosocial determinants, genital hygiene, path analysisCorrespondence: